Characterization of Humanitarian Trauma Care by US Military Facilities During Combat Operations in Afghanistan and Iraq. Issue 4 (15th October 2022) - Gurney, Jennifer M.; Graf, Victoria; Staudt, Amanda M.; Trevino, Jennifer D.; VanFosson, Christopher A.; Wild, Hannah; Wren, Sherry M.
Abstract : Objective: To characterize humanitarian trauma care delivered by US military treatment facilities (MTFs) in Afghanistan and Iraq during combat operations. Background: International Humanitarian Law, which includes the Geneva Conventions, defines protections and standards of treatment to victims of armed conflicts. In 1949, these standards expanded to include injured civilians. In 2001, the Global War on Terror began in Afghanistan and expanded to Iraq in 2003. US MTFs provided care to all military forces, civilians, and enemy prisoners. A thorough understanding of the scope, epidemiology, resource requirements, and outcomes of civilian trauma in combat zones has not been previously characterized. Methods: Retrospective cohort analysis of the Department of Defense Trauma Registry from 2005 to 2019. Inclusion criteria were civilians and Non–North Atlantic Treaty Organization (NATO) Coalition Personnel (NNCP) with traumatic injuries treated at MTFs in Afghanistan and Iraq. Patient demographics, mechanism of injury, resource requirements, procedures, and outcomes were categorized. Results: A total of 29, 963 casualties were eligible from the Registry. There were 16, 749 (55.9%) civilians and 13, 214 (44.1%) NNCP. The majority of patients were age above 13 years [26, 853 (89.6%)] and male [28, 000 (93.4%)]. Most injuries were battle-related: 12, 740 (76.1%) civilians and 11, 099 (84.0%) NNCP. Penetrating trauma was the most common cause of both battle and nonbattle injuries: 12, 293 (73.4%) civilian and 10, 029 (75.9%) NNCP. Median Injury Severity Score (ISS) was 9 in each cohort with ISS≥25 in 2236 (13.4%) civilians and 1398 (10.6%) NNCP. Blood products were transfused to 35% of each cohort: 5850 civilians received a transfusion with 2118 (12.6%) of them receiving ≥10 units; 4590 NNCPs received a transfusion with 1669 (12.6%) receiving ≥10 units. MTF mortality rates were civilians 1263 (7.5%) and NNCP 776 (5.9%). Interventions, both operative and nonoperative, were similar between both groups. Conclusions: In accordance with International Humanitarian Law, as well as the US military's medical rules of eligibility, civilians injured in combat zones were provided the same level of care as NNCP. Injured civilians and NNCP had similar mechanisms of injury, injury patterns, transfusion needs, and ISS. This analysis demonstrates resource equipoise in trauma care delivered to civilians and NNCP. Hospitals in combat zones must be prepared to manage large numbers of civilian casualties with significant human and material resources allocated to optimize survival. The provision of humanitarian trauma care is resource-intensive, and these data can be used to inform planning factors for current or future humanitarian care in combat zones.